9 - (Re)Venturing into the Public Sphere: Historical Sociology of ‘August Meeting’ among Igbo Women in Nigeria - Odoemene, Akachi (Africa Development, 2021)
August meetings, the annual mothers’ congresses held in the month of August, witness massive home-coming of ‘Igbo women’ to their marital rural hometowns, where they unite with their rural-based colleagues for community development purposes. However, they have of recent delved into the hitherto public sphere domains exclusive to the men-folk. Indeed, these truly typify the rise of women as a social force and their conscious pursuit of development. But, how truly participatory are they? To what extent have they empowered the women-folk in the public sphere? This study articulates the idea of the public sphere within the Igbo context and develops a comprehensive analysis and view of the agency of women’s participation therein, by focusing on their grassroots initiatives and the crucial roles they play in societal development. It analyses the history and evolution of the ‘August Meeting’, throwing light on its structure, functions and operational modes. It further demonstrates the degree of this meeting’s autonomy from men’s groups, and highlights the factors that inhibit these women in further negotiating a space in the public sphere. It concludes that the ‘August Meeting’ has a critical mandate in Igbo political affairs and re resents the socio-economic and cultural development initiative of women.